Identification of hepatitis B virus genotype I in Thailand. Issue 4 (8th November 2018) - Holzmayer, Vera; Hance, Robert; Defechereux, Patricia; Grant, Robert; Kuhns, Mary C.; Cloherty, Gavin; Rodgers, Mary A.
Abstract : The rare hepatitis B virus genotype I (HBV‐I) classification includes complex A/G/C/U recombinants identified amongst the individuals from China, India, Laos, and Vietnam. Herein we report the first HBV‐I specimen from Thailand, with detectable HBsAg despite a 10–amino‐acid truncation. This HBV‐I genome has a similar recombinant pattern to reference strains, including a C region that branches basal to references, suggesting a premodern era recombination event gave rise to HBV‐I. With an average sequence divergence from other genotypes ranging from 7.66% (standard deviation [SD], 0.42%; C) to 14.27% (SD, 0.31%; H), this new genome supports the HBV‐I classification as a unique genotype.